2005
DOI: 10.1016/j.molcel.2005.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for RACK1 Mediates Activation of JNK by Protein Kinase C

Abstract: There was an error in the Experimental Procedures section under the subheading "Crystallization." The complex cocrystals were obtained with a final DNA concentration of 0.85 mM (not nM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 0 publications
8
112
1
Order By: Relevance
“…After treatment of cells with ultraviolet B or anisomysin, we also observed that the low c-Jun level in siRack1 cells is a general phenomenon (Supplementary Figure S2C). Others have reported that JNKs activity is decreased after Rack1 knockdown (Lopez-Bergami et al, 2005). However, our results indicated that Rack1 knockdown in JB6 cells had no effect on JNKs phosphorylation or JNKs activity toward its substrate ATF2 (Supplementary Figure S2C), which suggested that the low c-Jun protein level is not related to JNKs activity in JB6 cells.…”
Section: Rack1 Promotes Cell Transformation By Maintaining C-jun Protcontrasting
confidence: 65%
See 1 more Smart Citation
“…After treatment of cells with ultraviolet B or anisomysin, we also observed that the low c-Jun level in siRack1 cells is a general phenomenon (Supplementary Figure S2C). Others have reported that JNKs activity is decreased after Rack1 knockdown (Lopez-Bergami et al, 2005). However, our results indicated that Rack1 knockdown in JB6 cells had no effect on JNKs phosphorylation or JNKs activity toward its substrate ATF2 (Supplementary Figure S2C), which suggested that the low c-Jun protein level is not related to JNKs activity in JB6 cells.…”
Section: Rack1 Promotes Cell Transformation By Maintaining C-jun Protcontrasting
confidence: 65%
“…Through its WD40 domains, Rack1 can bind one or two other molecules to form a complex that has an important role in various cellular functions (Schechtman and Mochly-Rosen, 2001). For example, Rack1 functions as an adaptor protein between activated protein kinase C and JNKs to enhance JNKs phosphorylation (Lopez-Bergami et al, 2005) and regulates translation as a component of the 80S ribosome (Sengupta et al, 2004). Rack1 also promotes degradation of HIF1a (Liu et al, 2007) and BimEL (Zhang et al, 2008) by mediating the interaction between each of these proteins and the ubiquitin complex.…”
Section: Introductionmentioning
confidence: 99%
“…As PKC is known to both scaffold with and phosphorylate JNK (Lopez-Bergami et al, 2005;Ping, 2003;Pontrelli et al, 2004), we propose that in wild-type mice, morphine recruitment of PKC activates JNK but that barrestin 2 recruitment limits further JNK activation. However, if b-arrestin 2 is absent and is coupled with the inability of morphine to recruit b-arrestin 1 (Groer et al, 2011), sufficient PKC recruitment results in sustained activation of the JNK cascade in b-arr2À/À neurons to affect analgesia.…”
Section: Discussionmentioning
confidence: 94%
“…Bax and JNK are binding partners of RACK1 (28,60). Currently it is still not clear how these proteins interact and act during IBDV infection.…”
Section: Discussionmentioning
confidence: 99%